A Novel Pumped Hydro Combined with Compressed Air Energy Storage System - Erren Yao; Xinbing Wang; Liqin Wang; Huanran Wang (Energies, 2013)
A novel pumped hydro combined with compressed air energy storage (PHCA) system is proposed in this paper to resolve the problems of bulk energy storage in the wind power generation industry over an area in China, which is characterised by drought and water shortages. Thermodynamic analysis of the energy storage system, which focuses on the pre-set pressure, storage volume capacity, water air volume ratio, pump performance, and water turbine performance of the storage system, is also presented. This paper discovers how such parameters affect the performance of the whole system. The ideal performance of this novel system has the following advantages: a simple, highly effective and low cost structure, which is comparable to the efficiency of a traditional pumped hydro storage system. Research results show a great solution to the current storage constraints encountered in the development of the wind power industry in China, which have been widely recognised as a bottleneck in the wind energy storage industry.